PEMBUATAN PULP DAN KERTAS DARI KULIT DURIAN - PERDINAN SINUHAJI; JUNEDI GINTING; MELYA DYANASARI SEBAYANG (Jurnal Poli-Teknologi, 2014)
A test on the production of pulp and paper from durian hides has been carried out with cooking temperature of 135 oc for a duration of 1.5 hours in a liquid of 2% : 3% : 4% naoh with comparison of durian hide fragment : cooking liquid 1 : 6. Durian hides possesses grinding level of 180 csf ,cracking index of 0.6 kpa.m2/gr and low tension index namely 15 nm/gr. The composition of the mixture of durian hide pulp ( 3% naoh ) with old currugated carbon ( occ) is (100% : 0) ;(90% : 10%); (80% : 20%), (70% : 30%). To the grinding level of 300 ml csf, starch of 1% and sizing agent(akd) 1% is added. Physical characteristics of the paper sheet possesses gramature of 54.5 gr/m2,thickness 0.321 mm, tensile strength 1.13 kn/m, tearing strength 253 mn, porosity( bensten)2050 ml/minute and roughness (bensten) 1700 ml/minute. The paper grammage had not fulfilled basic paper specification for plastic laminated wrapping paper, sni 14-6519-2001. Keyword : durian hides, pulp, paper